STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI TANTANGAN ERA REVOLUSI INDUSTRI 4.0 - Ifadah, Luluk; Tri Utomo, Sigit (STAINU Purworejo, 2019)
Changes and accelerations in the progress of information technology in the industrial revolution era 4.0 with the characters simple, faster, cheaper and Accessible bring changes in the meaning of life in the context of Islamic religious education, especially in the use of appropriate learning strategies so as to be able to answer challenges in the digital age. The method used in this research was carried out with literature study through hermeneutic analysis so that it was able to capture the meaning, values ​​and intentions contained in the learning strategies of Islamic education in facing the challenges of the industrial revolution era 4.0. In addition, the authors use content analysis, namely research conducted on information that is carried out data analysis and scientific processing. The results showed that the challenges faced in learning PAI in the industrial revolution 4.0 era included reduced direct interaction between teachers and students, the role of teachers displaced by technology. learners lose the attitude of tawadhu 'and the concept of the blessing of science to the teacher, the erosion of the value of spirituality in learning, the teacher must be able to become a role model for students so that students do not lose role models in the reality of their lives, the blurring of scientific knowledge from references obtained through Digital Digital media. The learning strategies used by Islamic religious education teachers in facing the challenges of the industrial revolution 4.0 era include: Teachers provide learning with Blended learning. Students are given the opportunity to complete web-based tasks and Email., Teachers teach with Word Processor (WP), Teachers provide Web-Based Learning (WBL) that can be used in CBI (Computer Based Instruction) or CAI (Computer Assisted Instruction), Teachers provide online-based guidance and direction through social media product facilities